Efektifitas Media Penukar Ion Zeolit Dan Ferolit Dalam Menurunkan Kadar Fe Air Sumur - Sri Mulyono; Wiwiek Mulyani; Ferry Kriswandana (FORIKES, 2020)
The quality of clean water and drinking water is greatly influenced by the type of soil and pollution of raw water. Groundwater often contains large amounts of iron (Fe) and manganese (Mn). The presence of Fe and Mn in water causes the water to turn brownish yellow after a while of contact with air. In the Keerom Regency area there are still many clean water facilities whose quality does not meet the health requirements, based on preliminary data in the Pir I Arso City area, the chemical quality of water has not met the requirements, namely very high Fe levels found Fe levels of 4.629 mg / liter which exceed levels maximum. To reduce Fe levels in well water, it is necessary to do research. Whether each ion exchange medium with different thicknesses is effective in reducing Fe levels in well water, it is necessary to make a contact filtration design with zeolite and ferolite media which is believed to reduce Fe levels in well water. This type of research is an experiment with a pretest-posttest design with a control group design. The material used in this study was an experimental pretest-posttest design with a control group design. The materials used in this study were ion exchange media in the form of zeolite, resin and ferolite, resident water in Arso PIR II. The data collected were primary data, namely Fe levels before and after going through contact filtration treatment. The data were analyzed statistically by means of paired test, ANOVA and linear regression, the error rate was set at α